ENHANCING INTERDISCIPLINARY COLLABORATION IN EMERGENCY MEDICAL RESPONSE: INTEGRATING TECHNICIAN EMS, PHARMACY, SOCIOLOGY, AND NURSING EXPERTISE - Nasser Saleh D Al Qrban, Ahmed Mahdi Hassain Al Sallum, Mahdi Hamad Mahdi Alsleam, Mesfer Mohammed Hadi Al thaiban Jamilah Jazzaa Shulaywih Alanazi, Reem Ibrahim Abdullah Aldoosary,,; Mansour Mohamed Alhareth, Mesfer Mohammed Mushabbab Alwalah, Fatimah Malouh Mutir Alonzi, Mohammed Hussain Ali Alzogli, (Chelonian Research Foundation, 2022)
Background: Effective emergency medical response relies on the collaboration Qfvarious healthcare professionals, including emergency medical services (EMS) technicians, pharmacy professionals, sociologists, and nurses. Interdisciplinary collaboration enhances the efficiency and quality ofpatient care in critical situations. This research paper explores strategies to enhance interdisciplinary collaboration in emergency medical response by integrating the expertise of these diverse healthcare professionals. Methods: The study employed a mixed-methods approach to investigate interdisciplinary collaboration in emergency medical response. Qualitative data were gathered through interviews and focus groups with EMS technicians, pharmacy prefessi onals, sociologists, and nurses to explore their perspectives on collaboration. Quantitative data were collected through surveys to assess the effectiveness of collaboration strategies. Integration methods included team-based training programs, cross-disciplinary workshops, and joint emergency simulations. Results: The findings reveal that interdisciplinary collaboration positively impacts emergency medical response by improving response times, enhancing patient care quality, and optimizing treatment outcomes. Stakeholders expressed satisfaction with collaborative practices, emphasizing improved communication, coordination, and mutual understanding among healthcare professionals. Survey results indicated a high level ofagreement among participants regarding the effectiveness Of integration methods in promoting interdisciplinary collaboration. Discussion: The results underscore the importance of interdisciplinary collaboration in emergency medical response and highlight the significant role of EMS technicians, pharmacy professionals, sociologists, and nurses in providing optimal patient care, The study identifies key implications for healthcare practice, including the need for ongoing education and training initiatives, interdisciplinary research partnerships, and policy reforms to support collaborative practices. Future directions include further exploration of collaboration models, evaluation of long-term outcomes, and dissemination of best practices to enhance emergency medical care delivery. Keywords: interdisciplinary collaboration, emergency medical response, EMS, pharmacy, sociology, nursing.